The intensive and the extensive margins: not only an international issue. - Arespa-Castelló, Marta (Springer, 2013)
Empirical evidence shows that quantity (intensive margin) and variety availability (extensive margin) have effects of different magnitude on populations’ welfare. Indeed, the pattern of a market dynamics may cause changes in welfare inequality. Low income consumers benefit more from quantity than high income consumers, who are more interested in enjoying variety. These facts have been usu- ally addressed as consequences of trade liberalization by international trade theory. However, market dynamics are also present within the borders of every country. It is important to understand what forces, unrelated with international trade, affect these dynamics. This paper explores the transmission of different real shocks into mar- ket dynamics in a new-Keynesian closed economy. Results show that the source of the shock is crucial to determine the magnitude and direction of the effects on each margin.
Keywords: Comercio; Mercados; Consumidores; Extensive margin; Innovation; Market dynamics; Endogenous entry; Real shocks